The expansion and loss of specific olfactory genes in relatives of parasitic lice, the stored-product psocids (Psocodea: Liposcelididae) - Jun Sun; Jian Wu; Sheng-Yuan Sun; Zhi-Dong Chen; Guy Smagghe; Jin-Jun Wang; Dan-Dan Wei (BMC Genomics)
Abstract Background Booklice, belonging to the genus Liposcelis (Psocodea: Liposcelididae), commonly known as psocids, infest a wide range of stored products and are implicated in the transmission of harmful microorganisms such as fungi and bacteria. The olfactory system is critical for insect feeding and reproduction. Elucidating the molecular mechanisms of the olfactory system in booklice is crucial for developing effective control strategies. In this study, we aim to bridge this knowledge gap by leveraging the transcriptome and genome data from five Liposcelis species. Result Using HMMER method and manual annotation, we have identified common gene families associated with olfactory processes, including odorant binding proteins (OBPs), chemosensory proteins (CSPs), odorant receptors (ORs), ionotropic receptors (IRs), and sensory neuron membrane proteins (SNMPs). Specifically, we identified 94, 118, 26, 47, and 34 olfactory-related genes in L. bostrychophila, L. tricolor, L. entomophila, L. decolor, and L. yangi, respectively. Comparison of quantities revealed that the number of ORs and IRs in the genome is significantly higher than those identified in the transcriptome. This discrepancy may be due to the specific expression of these genes in certain tissues or their lack of expression during the experimental stage. Simultaneously, analysis of gene expression profiles across different developmental stages revealed varying periods of peak expression for olfactory-related genes. These results suggest that the identification of olfactory-related genes in booklice on a genome-wide scale is more feasible and reliable than using a transcriptome-based approach. Additionally, compared to parasitic lice, booklice possess significantly more olfactory-related genes. This increase may be due to the inability of parasitic lice to survive without a host, whereas booklice have a wide range of feeding habits and live in complex and variable environments. Furthermore, we observed that the IR gene family in L. tricolor has undergone a certain degree of amplification, which may facilitate its adaptation to diverse environmental conditions. Conclusions We identified olfactory-related genes of five Liposcelis species for the first time, providing valuable insights for future functional investigations into olfactory genes associated with pheromone and odorant recognition. These discoveries present promising targets for effectively managing psocid pests.